IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN TEMATIK TERPADU TEMA INDAHNYA NEGERIKU SUB TEMA KEANEKARAGAMAN HEWAN DAN TUMBUHAN KELAS IV SEMESTER 2 SDN TOMPOMULYO 02 KABUPATEN PATI - Mudzanatun, Mudzanatun; Kurniasih, Eka (Universitas PGRI Semarang, 2014)
This research is motivated by the lack of knowledge of teachers in the implementation of the curriculum in 2013 on the learning process. Teachers do not understand fully the curriculum in 2013, because of socialization of the service is still lacking.The problem in this study is how the implementation of the curriculum in 2013 of integrated thematic learning on the theme?óÔé¼?ØIndahnya Negeriku?óÔé¼?Ø Sub Theme ?óÔé¼?ôKeanekaragaman Hewan dan Tumbuhan?óÔé¼?Ø class IV in the 2nd half of the fourth grade students of SDN Tompomulyo 02?. The purpose of this study is to investigate the implementation of the curriculum in 2013 on the theme of integrated thematic learning on the theme?óÔé¼?ØIndahnya Negeriku?óÔé¼?Ø Sub Theme ?óÔé¼?ôKeanekaragaman Hewan dan Tumbuhan?óÔé¼?Ø class IV in the 2nd half of the fourth grade students of SDN Tompomulyo 02.This research uses descriptive qualitative research approach that is research data collection in the form of words. Location of the study in 02 Pati SDN Tompomulyo fourth grade 2nd semester.Data sourced words research results. The average percentage of lesson plans prepared by teachers good observer I category with a percentage of 82,21%, a good observer II category with a percentage of 81,77% . The average percentage of the implementation of learning that teachers do a good observer I category with a percentage of 82,19%, a good observer II category with a percentage of 8,.43%. Assessment of learning evaluation conducted after a study showed that six of 21 people there are 10 students or 47,62% to the category of very good, good category there are 5 students with a percentage of 23,80%, good enough category there are 4 students with a percentage of 19,05%, unfavorable category there are 2 students or 9,53%, and there were no students in the category of bad result.Suggestions given to teachers , learners and the school is implementing in order to further develop the learning in the classroom in accordance with the implementation of the curriculum in 2013 .